Transformasi Gaya Hidup Aktif di Era Digital: Analisis Literatur pada Pendidikan Jasmani Sekolah - Akbar, Andi Khemal; Mulyaningsih, Eka (Institut Agama Islam Negeri (IAIN) Bone, 2025)
The advancement of digital technology has significantly influenced various aspects of life, including a shift in students’ lifestyles toward increased sedentary behavior. This article aims to analyze the transformation of students’ active lifestyles in the digital era and its implications for physical education practices in schools. Using a library research approach and content analysis of relevant literature, findings indicate a negative correlation between intensive digital technology use and students’ physical activity levels and interest in physical education. However, digitalization also presents pedagogical opportunities, such as the integration of gamification, fitness applications, and project-based learning, which can enhance student participation and motivation. The study highlights the importance of adaptive, relevant, and digital-friendly teaching strategies in physical education. It recommends a transformation of curricula and instructional methods to maintain physical education’s relevance in promoting healthy lifestyles amid digital dominance. Thus, physical education can play a strategic role in balancing technological advancement with students’ physical well-being. Perkembangan teknologi digital telah memengaruhi berbagai aspek kehidupan, termasuk perubahan gaya hidup siswa yang semakin sedentari. Artikel ini bertujuan untuk menganalisis transformasi gaya hidup aktif siswa di era digital dan implikasinya terhadap praktik pendidikan jasmani di sekolah. Melalui pendekatan studi kepustakaan dengan analisis isi terhadap literatur relevan, ditemukan bahwa penggunaan teknologi digital secara intensif berkorelasi negatif dengan tingkat aktivitas fisik dan minat siswa terhadap pelajaran jasmani. Namun demikian, digitalisasi juga menawarkan peluang pedagogis, seperti integrasi gamifikasi, aplikasi kebugaran, dan pembelajaran berbasis proyek yang mampu meningkatkan partisipasi dan motivasi siswa. Hasil kajian menunjukkan pentingnya strategi pembelajaran yang adaptif, relevan, dan digital-friendly dalam pendidikan jasmani. Penelitian ini merekomendasikan transformasi kurikulum dan metode pengajaran pendidikan jasmani yang lebih kontekstual agar tetap mampu membentuk gaya hidup sehat di tengah dominasi teknologi. Dengan demikian, pendidikan jasmani dapat berperan strategis dalam menjaga keseimbangan antara kemajuan digital dan kesehatan fisik siswa.